2004
DOI: 10.1258/095646204774195218
|View full text |Cite
|
Sign up to set email alerts
|

Is telephone follow-up as good as traditional clinic follow-up in achieving the proposed national outcome standards for chlamydia management?

Abstract: A retrospective review of 400 cases of genital chlamydia managed with a traditional clinic follow-up was compared to 400 cases with a telephone follow-up appointment. We satisfactorily treated more patients with the telephone follow-up appointment than with a traditional clinic follow-up (204 [51%] vs 121 [30%]; P <0.0001). We also satisfactorily treated more partners with the telephone follow-up system than a traditional clinic appointment system (0.57 vs 0.45 contacts per case; P =0.0006). The introduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…Indeed, this appears to be confirmed by previous studies, which showed that partner contact and treatment were more effective among younger patients. 17 However, another study reported that older patients were more inclined to inform their sexual partners. 18 In our study, other reasons may include the difficulty to communicate with foreign patients due a lack of understanding of French.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this appears to be confirmed by previous studies, which showed that partner contact and treatment were more effective among younger patients. 17 However, another study reported that older patients were more inclined to inform their sexual partners. 18 In our study, other reasons may include the difficulty to communicate with foreign patients due a lack of understanding of French.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the effectiveness of existing systems does not necessarily require the introduction of complex ICT (e.g. use of telephone follow-up for chlamydia 24 ). Older technologies such as the telephone also remain the most popular choice for booking a clinic appointment and suggest that the introduction of new ICT should incorporate the views of patient and community groups and be performed in parallel with a more general review of patient pathways and clinic systems.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up interview can be performed by phone or other means of communication or in person 68,69 (III, B). Patients who remain symptomatic, who have not completed their medication or who have had unprotected sexual intercourse with an untreated partner should be asked to return to the clinic and re-treated with appropriate contact tracing (IV, C).…”
Section: Follow-up For Patients With Ngumentioning
confidence: 99%
“…Follow-up after 2-3 weeks is important in order to assess compliance with therapy, ensure resolution of symptoms and to assess the risk of re-infection from an untreated partner, particularly in chlamydia-positive patients. The follow-up interview can be performed by phone or other means of communication or in person 68,69 (III, B). Patients who remain symptomatic, who have not completed their medication or who have had unprotected sexual intercourse with an untreated partner should be asked to return to the clinic and re-treated with appropriate contact tracing (IV, C).…”
Section: Follow-up For Patients With Ngumentioning
confidence: 99%